Effect of growth time on structural and surface properties of TiO2 nanostructures deposited by single-step hydrothermal method. (2022) - Mezzourh, H.; Ben Moumen, S.; Amjoud, M.; Mezzane, D.; El Amraoui, Y.; Marbati, B.; Lahmar, A.; Jouiad, M.; El Marssi, M.
Abstract: In this study, highly pure rutileTiO2 nanorods (NRs) structures were grown on fluorine-doped tin oxide (FTO) coated glass substrates by using a one-step hydrothermal method. The effect of the growth time on the structure and surface properties of the obtained products has been studied. The X-ray diffraction analysis and the Raman spectroscopy indicated that the films were single-crystalline rutile phase. At lower hydrothermal time, TiO2 NRs singly distributed with small diameter are found showing a high contact angle with ethylene glycol. When the hydrothermal reaction increases, nanoflowers (NFs) with a large diameter are formed over the TiO2 NRs leading to superhydrophilic surfaces. These nanostructured thin films can be tailored to the requirements of specific applications involving water and ethylene glycol.